(untitled) (مجلة المنصور, 2023)
Simulated annealing algorithm is a recent powerful technique for solving hard problems. Furthermore, if has a very interesting features: general applicability. In fact, it has been used successfully for solving many NP-complete problem. This paper describes elementary theoretical concepts and principles of this technique and presents. As well, some examples with results in which simulated annealing algorithm is used to solve hard problems .